Pengaruh Kepemilikan Manajerial, Komisaris Independen dan Komite Audit Terhadap Tax Avoidance - Fadila, Noriska Sitty; Pratomo, Dodi; Yudowati, Siska Priyandani (E-Jurnal Akuntansi, 2017)
Tax avoidance is mostly done by the tax-payer because it is legal. In this case there is not a violation of law, but can obtain the saving by avoid of tax. For companies, tax is expenses to reduce net profit of the company. Tax is the most biggest contributors of state income. In the goverment, tax avoidance could reduce the number of state revenue. This study aims to find out how the influence of managerial owned, board of commissioner and audit committee to tax avoidance.The population in the research is manufacturing companies are listed in the Indonesian Stock Exchange. By using purposive sampling in the observation period 2011-2014 with 11 sample. The data were analyze by using data panel regression with significance level 5%.The results of this study show that managerial owned and audit committeee has negative significant affect on tax avoidance. Other results show that the tax avoidance activity is not affected significantly by board of commissioner.
Keywords: Managerial Owned, Board of Commissioner, Audit Committee, Tax Avoidance, Book Tax Different.